2015
DOI: 10.1063/1.4922728
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of curvature and thickness on elastic wave velocity in cornea-like structures by finite element modeling and optical coherence elastography

Abstract: Wave models that have been used to extract the biomechanical properties of the cornea from the propagation of an elastic wave are based on an assumption of thin-plate geometry. However, this assumption does not account for the effects of corneal curvature and thickness. This study conducts finite element (FE) simulations on four types of cornea-like structures as well as optical coherence elastography (OCE) experiments on contact lenses and tissue-mimicking phantoms to investigate the effects of curvature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…The speed depends on in-plane tension and Young's modulus, as well as geometrical factors such as the size, curvature and thickness [21]. The measured resonance peaks seem to fit well with the circular membrane theory [22] Fig.…”
Section: Resultssupporting
confidence: 57%
“…The speed depends on in-plane tension and Young's modulus, as well as geometrical factors such as the size, curvature and thickness [21]. The measured resonance peaks seem to fit well with the circular membrane theory [22] Fig.…”
Section: Resultssupporting
confidence: 57%
“…E=2Ļfalse(1+Ļ…false)3(0.87+1.12Ļ…)2cg2, where Ļ was the density of the material ( Ļ =1000 kg/m 3 for the agar phantoms and Ļ =1062 kg/m 3 for the cornea [65]), Ī½ =0.49 was the Poissonā€™s ratio to account for the nearly incompressible nature of the phantoms and corneas [66], and c g was the elastic wave group velocity. Spectral analysis was utilized to provide depth-resolved elasticity mapping [51].…”
Section: Methodsmentioning
confidence: 99%
“…For example, finite-element modelling (FEM) supported by experimental data showed that taking account of the stress at the tissue surface, e.g., imparted by a fluid, significantly reduced the group velocity of the elastic wave and, thus, could produce errors in quantification of elastic properties [109,111]. Geometrical factors, such as tissue curvature and thickness, also have profound effects on the measured elastic wave speed [105]. Han et al performed a systematic analysis of the accuracy of four analytical models and FEM for extracting the elastic modulus of soft samples [45].…”
Section: Surface Elastic Wave Methods and Applicationsmentioning
confidence: 99%
“…Point dynamic loading is attractive as a source of shear waves, and an attractive noncontact localized method is the micro-air puff developed and applied extensively by the Larin group [45, 57, 63, 81, [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116], mainly to the cornea, but also to skin [108,116], cardiac and skeletal muscles [104], cartilage [101,106], fat and soft tissue tumors [97], and kidneys [112]. Similar to ARF-based excitation, an air puff can deliver a localized and well-controlled impulse stimulus, which can be accompanied by measurement of the tissue displacement or measurement of the air puff-induced elastic wave.…”
Section: Loading Methodsmentioning
confidence: 99%